2015
DOI: 10.1007/s12517-015-2003-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing spatial variability of soil properties in salt affected coastal India using geostatistics and kriging

Abstract: Soil salinization is a major problem affecting 955 Mha globally and 7 Mha in India. Soil properties vary spatially and knowing the extent of spatial variability of soil physicochemical characteristics is highly essential for management of these soils and crop cultivation. This study was conducted in salt-affected coastal parts of eastern India, with the following objectives: (i) to explore the spatial variability of soil properties (soil electrical conductivity (ECe), soil pH, soil organic carbon (SOC), availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 26 publications
3
36
0
1
Order By: Relevance
“…In India majority of soil maps were prepared by conventional methods and a very little work has been done so far to use the modern spatial prediction techniques in this regard (Saha et al 2012;Pal et al 2014;Behera and Shukla 2015;Tripathi et al 2015;Bhunia et al 2016). The accurate estimation of spatial distribution of soil properties [soil pH, organic carbon (OC), electrical conductivity, phosphorous, potassium, etc.]…”
Section: Introductionmentioning
confidence: 99%
“…In India majority of soil maps were prepared by conventional methods and a very little work has been done so far to use the modern spatial prediction techniques in this regard (Saha et al 2012;Pal et al 2014;Behera and Shukla 2015;Tripathi et al 2015;Bhunia et al 2016). The accurate estimation of spatial distribution of soil properties [soil pH, organic carbon (OC), electrical conductivity, phosphorous, potassium, etc.]…”
Section: Introductionmentioning
confidence: 99%
“…Havlin et al, (2005) reported that organic matter increases P by anion replacement of H 2 PO 4 − ion on adsorption sites and increasing the quantity of organic P mineralized to inorganic P. Phosphorus showed moderate variation in both normal and salt affected soils as indicated by CV values. Tripathi et al, (2015) have reported medium range of variation in available P with CV value of 25.95%.…”
Section: Available Phosphorusmentioning
confidence: 92%
“…The coefficient of variation varied sharply with depth indicating lateral and vertical variation. Tripathi et al, (2015) have reported medium range of variation in available K with CV value of 36.67%.…”
Section: Available Potassium (K)mentioning
confidence: 92%
See 2 more Smart Citations